2023
DOI: 10.1186/s12575-023-00223-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of exosome protein panels as predictive biomarkers for non-small cell lung cancer

Bin Luo,
Zujun Que,
Xinyi Lu
et al.

Abstract: Background Non-small cell lung cancer (NSCLC) remains a leading cause of cancer-related deaths worldwide, primarily due to its propensity for metastasis. Patients diagnosed with localized primary cancer have higher survival rates than those with metastasis. Thus, it is imperative to discover biomarkers for the early detection of NSCLC and the timely prediction of tumor metastasis to improve patient outcomes. Methods Here, we utilized an integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Further enriching the diagnostic toolkit, Jin et al's study on urine exosomes identified differential expression of WASL, STK10, and WNK1 as potential lung cancer biomarkers [177]. These findings, along with the identification of FGB, FGG, and VWF in exosome panels, fortify the prospect of early NSCLC diagnosis and shed light on the correlation of survival duration, emphasizing the significance of exosomal proteins in lung cancer prognosis [178].…”
Section: Clinical Application Potential Of Lung Cancer Exosome Proteo...mentioning
confidence: 95%
See 1 more Smart Citation
“…Further enriching the diagnostic toolkit, Jin et al's study on urine exosomes identified differential expression of WASL, STK10, and WNK1 as potential lung cancer biomarkers [177]. These findings, along with the identification of FGB, FGG, and VWF in exosome panels, fortify the prospect of early NSCLC diagnosis and shed light on the correlation of survival duration, emphasizing the significance of exosomal proteins in lung cancer prognosis [178].…”
Section: Clinical Application Potential Of Lung Cancer Exosome Proteo...mentioning
confidence: 95%
“…Moreover, the identification of CFHR5, C9, and MBL2 as biomarkers for NSCLC metastasis assessment, along with interleukin-34, HLA-DMA, and HLA-DOB in serum exosomes, underscores the intricate role of exosomal proteins in NSCLC progression and immune system interactions [178,179]. This finding is complemented by the correlation of FAM166B, Killer Cell Immunoglobulin-like Receptor 2DL1, and Olfactory Receptor 52R1 with lymph node metastasis, providing a prognostic perspective on NSCLC metastatic spread [179].…”
Section: Clinical Application Potential Of Lung Cancer Exosome Proteo...mentioning
confidence: 99%